2022
DOI: 10.1186/s41043-022-00296-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional habits according to age and BMI of 6–17-year-old children from the urban municipality in Poland

Abstract: Background Balanced nutrition is crucial for adolescent’s proper physical and mental development. Dietary habits change significantly with a child’s development. Along with increasing age and the shift towards adolescence, unhealthy diet-related habits become more common. The objective of the survey study was to determine the differences in nutritional habits between children and adolescents according to their age and body mass index (BMI). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(32 reference statements)
2
4
0
Order By: Relevance
“…Processed meat products, such as ham, sausages were more frequently consumed by the control group children than increased PA. Children with increased PA at school ate poultry meat more often and red meat less often than the control group ones. Lower consumption of poultry meat was observed also in the study by Basiak-Rasała et al, (2022) [ 61 ].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Processed meat products, such as ham, sausages were more frequently consumed by the control group children than increased PA. Children with increased PA at school ate poultry meat more often and red meat less often than the control group ones. Lower consumption of poultry meat was observed also in the study by Basiak-Rasała et al, (2022) [ 61 ].…”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, it decreased over time. Even less frequent fish intake was reported in the study of Basiak-Rasała (2022) [ 61 ]. The studies by Całyniuk et al, (2014) and Dortch et al, (2014) showed that regular PA was associated with higher consumption of meat, fish, wholemeal bakery products and vegetables [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Both soft drinks and sweet/salty snacks belong to UPFs which according to NOVA classification, are “made mostly or entirely from substances derived from foods and additives, with little if any intact edible parts of plants or animals minimally modified/preserved” [ 26 ]. As anticipated, and in accordance with the global trends, results showed that Greek preadolescents follow unhealthy dietary habits [ 1 , 27 , 28 ], whereas boys were found to be more susceptible to soft drinks and sweet/salty snacks compared to girls [ 29 , 30 ] perhaps due to the difference in response to environmental food cues, and in particular in high energy density foods [ 31 ]. The role of familial aggregation of unhealthy dietary habits is also re-confirmed, highlighting the effect of the family environment in the emotional/relational context [ 32 ], as well as the impact of aggressive marketing [ 33 ] addressed to youths.…”
Section: Discussionsupporting
confidence: 60%